The Refugee Dilemma: Refugee Rights versus State Security in Uganda - Ahimbisibwe, Frank (Research Journal of Social Science and Management, 2013)
Refugees, who were traditionally conceived and presented as humanitarian issues, are now increasingly being viewed as security threats. The language of threat now dominates refugee discourse and policy making as well as scholarly analysis. Focusing on Uganda, this paper explores how refugees have been reconstructed as security threats and the impact this reconstruction has had on refugee rights and protection. This paper argues that whereas the perception of refugees as a threat is valid, it is possible for this to be done without violating refugee rights. In otherwards, the protection of state security and refugee rights should be done concurrently without sacrificing any of the two
Keywords: Refugees; Human Rights; Protection; State; Security; Uganda